When the Façade of the Normal Falls Away - Alston, Kal (Philosophical Inquiry in Education, 2022)
The pandemic made us hold our breath for a return to “normal.” But education in “normal” times involves race-based violence and class-based inequality that the pandemic simply made plainer to see. Reviewing the impacts of the pandemic and action for racial justice over the last two years, I show how the dislocation of the “normal” laid bare what Riz Ahmed has called “a ‘normality’ of entitlement and extraction.